ALZHEIMER’S DISEASE TREATMENT WITH TRADITIONAL CHINESE MEDICINE - Zhu, Jihe; Arsovska, Blagica; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2019)
Alzheimer’s disease is a brain neurodegenerative disorder, which is characterized with coordinative and cognitive dysfunctions with significant loss of memory. By the terms of Traditional Chinese Medicine (TCM) the Alzheimer’s disease may occur because of: spleen or liver Qi deficiency with phlegm, spleen and kidney yang deficiency, Qi and blood stagnations and others. With the use of Ginkgo biloba the stagnated energy, the excretion of the mucus and blocked blood can be mobilized and the blood circulation can be promoted to the brain. This study includes 5 patients, 4 women and 1 man, aged from 55 to 78. All patients have the disease for more than 2 years and main symptom in all is dementia. All patients have done certain number of acupuncture treatment and were prescribed Ginkgo biloba 1g per day. After starting the treatment all patients have stated that their health condition is improved, their memory is better and are feeling warmth and circulation to the head and neck. For a chronic and lifetime disease like Alzheimer’s, the treatment with Gingko Biloba is also for lifetime and it is shown to be successful in its aim to slow down the progression of the disease and release the symptoms.